Pengaruh lama pemeraman dan dosis pupuk organik cair berbasis mol sayur dan buah terhadap pertumbuhan dan produksi tomat ceri (Solanum lycopersicum var. cerasiforme) - Farah Athaya Widha; Susilo Budiyanto; Endang Dwi Purbajanti (Department of Agriculture, Animal and Agricultural Sciences, Diponegoro University, Semara, 2018)
This research aimed to observe the response of different incubation period and dosage of liquid organic fertilizer (LOF) based on vegetable and fruit local microorganism on cherry tomato growth and production. This research was conducted at Operational Greenhouse, Balai Benih Pertanian Kota Semarang Gunung Pati, Semarang. The research was conducted by 3x3 factorial experiments with 3 replications. The first factor was 6, 12, 18 days of incubation period and the second factor was 120, 240, 360 ml/plant dosage of LOF. The observed parameters were fruit N uptake, plant height, fruit diameter and fruit fresh weight. Results of study showed that both treatments had no significant effect on fruit diameter and fruit fresh weight caused by lack of P in LOF so that the overall fruit production was not optimum. Interaction between both treatments showed significant effect on fruit N uptake when on short incubation period, the dosage used was higher and vice versa. Six days of incubation with 240 ml/plant dosage gave the highest efficiency on improving fruit N uptake. Incubation period has no significant effect but the dosage of 360 ml/plant significantly gave optimum effect on plant height in comparison with dosage of 120 and 240 ml/plant. This research can be concluded that LOF with 6 days of incubation with dosage used between 240-360 ml/plant was efficient to improve growth of cherry tomato plant and addition of fertilizer was needed to improve production of cherry tomato. Keywords : Cherry tomato, LOF incubation period, LOF dosage